Therapeutic targeting of autophagy in myocardial infarction and heart failure. (1st September 2016) - Riquelme, Jaime A.; Chavez, Myra N.; Mondaca-Ruff, David; Bustamante, Mario; Vicencio, Jose Miguel; Quest, Andrew F. G.; Lavandero, Sergio
ABSTRACT: Introduction : Myocardial infarction (MI) is the leading cause of death. When MI is not lethal, heart failure (HF) is a major consequence with high prevalence and poor prognosis. The targeting of autophagy represents a potentially therapeutic approach for the treatment of both pathologies. Areas covered : PubMed searches were performed to discuss the current state of the art regarding the role of autophagy in MI and HF. We review available and potential approaches to modulate autophagy from a pharmacological and genetic perspective. We also discuss the targeting of autophagy in myocardial regeneration. Expert commentary : The targeting of autophagy has potential for the treatment of MI and HF. Autophagy is a process that takes place in virtually all cells of the body and thus, in order to evaluate this therapeutic approach in clinical trials, strategies that specifically target this process in the myocardium is required to avoid unwanted effects in other organs.